2004
DOI: 10.1590/s0100-204x2004000700002
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxygenase activities during development of root and nodule of soybean

Abstract: -The objective of this work was to evaluate root and nodule soybean lipoxygenases in Doko cultivar and in a near isogenic line lacking seed lipoxygenases, inoculated and uninoculated with Bradyrhizobium elkanii. The lipoxygenase activities from roots collected at 3, 5, 9, 13, 18 and 28 days post-inoculation and from nodules collected at 13, 18 and 28 days post-inoculation were measured. The pH-activity profiles from root and nodules suggested that the lipoxygenases pool expressed in these organs from Doko cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…At the mRNA level, lipoxygenase was up-regulated under flooding but was steadily down-regulated during recovery. The slight increase in lipoxygenase at the protein level during recovery was considerably less than pre-flooding levels, confirming the role of this enzyme in growth and development of roots during germination, as reported earlier . The observed differences between protein abundance and mRNA expression suggest that post-translational modification affects the function of lipoxygenase.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…At the mRNA level, lipoxygenase was up-regulated under flooding but was steadily down-regulated during recovery. The slight increase in lipoxygenase at the protein level during recovery was considerably less than pre-flooding levels, confirming the role of this enzyme in growth and development of roots during germination, as reported earlier . The observed differences between protein abundance and mRNA expression suggest that post-translational modification affects the function of lipoxygenase.…”
Section: Discussionsupporting
confidence: 86%
“…The slight increase in lipoxygenase at the protein level during recovery was considerably less than pre-flooding levels, confirming the role of this enzyme in growth and development of roots during germination, as reported earlier. 44 The observed differences between protein abundance and mRNA expression suggest that post-translational modification affects the function of lipoxygenase. The slight increase in lipoxygenase suggests plant's attempt to resume growth suppressed by flooding.…”
Section: Cell Wall Metabolism-related Proteins Increase Lignification...mentioning
confidence: 99%
“…Interestingly, the molecular function enrichment was found for only linoleate 13S-lipoxygenase activity. This enzyme is involved in plant growth and development [15], and also in the wounding response through jasmonic acid (JA) signaling [16,17] (Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…The only observed difference is related to the presence of a band, of 95kDa molecular weight, in cultivar 'BRS267'. As studies dealing with electrophoresis of soybean grains proteins identified a lipoxygenase with molecular weight of 95kDa (JUNGHANS et al, 2004), it is possible that the band here verified corresponds to this protein. The catalytic action exerted by lipoxygenase on polyunsaturated fatty acids, linoleic and linolenic acid, of the soybean grains, is a major factor responsible for the appearance of carbonyl compounds, which promote the flavor of the grains (MARTINS et al, 2002).…”
Section: Resultsmentioning
confidence: 55%